Cognitive Behavioral Therapy for late-life depression (CBTlate): results of a multicenter, randomized, observer-blinded, controlled trial - Dafsari, Forugh Salimi; Bewernick, Bettina; Böhringer, Sabine; Domschke, Katharina; Elsaeßer, Moritz; Löbner, Margrit; Luppa, Melanie; Preis, Lukas; Püsken, Julia; Schmitt, Sandra; Szekely, Andreea-Johanna; Hellmich, Martin; et al. (Psychotherapy and psychosomatics, 2023)
Introduction: Different psychotherapeutic interventions for late-life depression (LLD) have been proposed, but their evaluation in large, multicenter trials is rare. Objective: The present study evaluated the efficacy of a specific cognitive behavioral therapy (CBT) for LLD (LLD-CBT) in comparison with a supportive unspecific intervention (SUI), both administered in a specialist psychiatric outpatient setting. Methods: In this randomized, controlled, parallel group trial, we recruited participants (≥60 years) with moderate to severe depression at 7 trial sites in Germany. Participants were randomly assigned to the LLD-CBT or SUI group. The primary outcome was depression severity at the end of treatment measured by change on the Geriatric Depression Scale (GDS). Secondary outcomes included change in observer-rated depression, anxiety, sleep ratings, and quality of life throughout the treatment phase and at 6-month follow-up. Results: Between October 1, 2018, and November 11, 2020, we randomly assigned 251 patients to either LLD-CBT (n = 126) or SUI (n = 125), of whom 229 provided primary-outcome data. There was no significant between-group difference in the change in GDS scores at the end of treatment (estimated marginal mean difference: −1.01 [95% CI: −2.88 to 0.86]; p = 0.287). Secondary analyses showed significant improvements in several outcomes after 8 weeks and at follow-up in both treatment arms. Conclusions: Our data suggest that LLD-specific CBT and a supportive unspecific treatment both provide clinical benefit in patients with moderate to severe LLD without evidence for superiority of LLD-CBT.